PENINGKATAN HASIL BELAJAR MATERI PERKALIAN SISWA KELAS III SD MELALUI MODEL NHT BERBASIS MEDIA ULAR TANGGA - Elintamaya, Eva; Sholihah, Husna Imro'athush; Munfariqoh, Aqidatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the multiplication learning outcomes of third-grade students at SDN 1 Karangtalun through the implementation of the NHT (Numbered Heads Together) model supported by multiplication snakes and ladders media. The subjects of this study were 15 third-grade students. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through observation, interviews, documentation, and tests. Data validity was ensured through source and method triangulation. The data were analyzed using qualitative and descriptive statistical techniques. The findings revealed that the implementation of the NHT (Numbered Heads Together) model assisted by multiplication snakes and ladders media improved both student participation and mathematics learning outcomes in multiplication material. This improvement was reflected in the increase of students’ cognitive learning outcomes from 33.33% in the pre-test to 73.33% in Cycle I and 86.67% in Cycle II. Student activity also increased from 21 points in Cycle I to 23 points in Cycle II. Therefore, the application of the NHT (Numbered Heads Together) learning model was proven effective in enhancing the quality of mathematics learning on multiplication material.